2011
DOI: 10.5047/eps.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Variation of ionospheric slab thickness observations at Chumphon equatorial magnetic location

Abstract: This study presents the diurnal and seasonal variations of slab thickness at the equatorial magnetic latitudes in Thailand during [2004][2005][2006], corresponding to the declining part of low solar activity. The GPS-derived total electron content (TEC) and the maximum electron density of the F-region (N m F 2 ) are used to compute the slab thickness (τ ) at the Chumphon station (10.72• N, 99.37• E), located near the magnetic equator. The results show that large peaks of slab thickness exist during the pre-sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Many other studies have reported for different longitudinal sectors that the ionospheric slab thickness also depends on diurnal, seasonal, solar activity, latitudinal and geomagnetic activity variations (e.g. Bhonsle et al, 1965;Titheridge, 1973;Kersley and Hajeb-Hosseinieh, 1976;Bhuyan et al, 1986;Davies and Liu, 1991;Jayachandran et al, 2004;Gulyaeva and Stanislawska, 2005;Kenpankho et al, 2011;Venkatesh et al, 2011). Jayachandran et al (2004) reported an ionosphere more thick during high solar activity when compared to low solar activity period.…”
Section: Introductionmentioning
confidence: 95%
“…Many other studies have reported for different longitudinal sectors that the ionospheric slab thickness also depends on diurnal, seasonal, solar activity, latitudinal and geomagnetic activity variations (e.g. Bhonsle et al, 1965;Titheridge, 1973;Kersley and Hajeb-Hosseinieh, 1976;Bhuyan et al, 1986;Davies and Liu, 1991;Jayachandran et al, 2004;Gulyaeva and Stanislawska, 2005;Kenpankho et al, 2011;Venkatesh et al, 2011). Jayachandran et al (2004) reported an ionosphere more thick during high solar activity when compared to low solar activity period.…”
Section: Introductionmentioning
confidence: 95%
“…EST provides an alternative way to interpret H. Once we have EST, we could estimate H and further the electron density profile. Thus, the spatial, temporal, and solar activity features of EST have been studied worldwide [Breed et al, 1997;Chuo et al, 2010;Dabas et al, 1993;Davies and Liu, 1991;Duarte-Silva et al, 2015;Goodwin et al, 1995aGoodwin et al, , 1995bGulyaeva, 2007;Gulyaeva et al, 2004;Jin et al, 2007;Kenpankho et al, 2011;Kouris et al, 2008;Stankov and Warnant, 2009]. Moreover, geomagnetic storms are also found to influence EST [e.g., Àlàgbé, 2012;Chuo et al, 2010;Gulyaeva, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Bhonsle et al, 1965;Titheridge, 1973;Huang, 1983). Based on most of the available and reliable observations of ionospheric TEC and NmF2, numerous analyses for recording the climatology of the slab thickness have been conducted over the past few decades (Jayachandran et al, 2004;Chuo, 2007;Jin et al, 2007;Stankov and Warnant, 2009;Guo et al, 2011;Kenpankho et al, 2011;Weng et al, 2012). Jayachandran et al (2004) investigated the variation in the slab thickness during the solar maximum and minimum phases of an intense solar cycle by using the hourly values of TEC and NmF2 at Hawaii (low latitude), Boulder (mid-latitude) and Goosebay (high latitude).…”
Section: Introductionmentioning
confidence: 99%